2016
DOI: 10.3171/2016.1.peds15534
|View full text |Cite
|
Sign up to set email alerts
|

Complications and safety of vagus nerve stimulation: 25 years of experience at a single center

Abstract: OBJECTIVE The goal of this paper was to investigate surgical and hardware complications in a longitudinal retrospective study. METHODS The authors of this registry study analyzed the surgical and hardware complications in 247 patients who underwent the implantation of a vagus nerve stimulation (VNS) device between 1990 and 2014. The mean follow-up time was 12 years. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 45 publications
1
89
0
4
Order By: Relevance
“…We found that HBOT was an efficient and safe adjuvant to antibiotics in the treatment of hardware-related infections, which allowed continued neuromodulation treatment and preservation of hardware following 12 out of 14 (86%) infection events in 10 out of 12 (83%) patients. This is a remarkable improvement in comparison to the outcomes in previous reports [7, 23-31], where hardware removal was undertaken for infection resolution in almost every instance (see Table 3 for comparison). Our results agree with the benefit of adjuvant HBOT reported in other neurosurgical infections such as cranial bone flap osteomyelitis [12, 32, 33] and spinal implants [34].…”
Section: Discussionmentioning
confidence: 60%
“…We found that HBOT was an efficient and safe adjuvant to antibiotics in the treatment of hardware-related infections, which allowed continued neuromodulation treatment and preservation of hardware following 12 out of 14 (86%) infection events in 10 out of 12 (83%) patients. This is a remarkable improvement in comparison to the outcomes in previous reports [7, 23-31], where hardware removal was undertaken for infection resolution in almost every instance (see Table 3 for comparison). Our results agree with the benefit of adjuvant HBOT reported in other neurosurgical infections such as cranial bone flap osteomyelitis [12, 32, 33] and spinal implants [34].…”
Section: Discussionmentioning
confidence: 60%
“…Whereas studies report rates of 1% to 5% of hardware malfunction 4 , these estimates are highly variable. Révész et al 40 published a 3% incidence of lead breakage, noticed mainly by the increase of seizure frequency, as not all fractures are identified on imaging screening. Infection rates vary from 3% to 7% and, although generally treated with intravenous antibiotics and explantation of the device, some have described success managing these patients exclusively with oral antibiotics.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…When comparing patients younger and older than 12 years, no significant difference in efficacy or complication rate was demonstrated after five years of follow-up in 141 patients 39 , although some reported increased infection rates in children 40 . Predictors of response have not been completely clarified, although some elements may have a prognostic value.…”
mentioning
confidence: 99%
“…The adverse effects are rather low at about 2%, usually occuring during the "on" phase of stimulation, and have a tendency to decrease over time. The most common complications are postoperative hematoma, infection, and vocal cord paralysis 7 . Voice hoarseness, cough and paresthesias can also occur 7 .…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%
“…Currently, more than 100,000 VNS devices have been implanted in more than 80,000 patients 7 . In Brazil, from January 2001 to March 2016, 665 VNS devices were implanted (Politec Health, personal communication).…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%